A theoretical base for urban morphology: Practical way to achive the city character - Vahid Ahmadi,; Hero Farkisch,; Adi Irfan,; Mastor Surat,; M. Fauzi M. Zain, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
The new cities form rapidly and usually follow many unconnected concepts that cause confusion in urban spaces while in historical cities formed gradually according to accepted patterns and corrected rules. Moreover, many non-local agents influence on the form of new cities while the forming of traditional urban spaces depends on the morphology of the site, the historical background and the culture of local people. In literature of urban design, character is synonymous with the concept of physical identity. Meaning is differences between physical traits of a city from other cities. Urban morphology has focused on urban physical studies, and provides a conceptual framework for urban character study. This process can be use, as the part of the urban spaces that have physical properties of the entire city instead of analyzed of the whole city. In this way, we were looking for some of the important researches by focus the urban morphology. We also had chosen the analysis literature review for our methodology. In this article, we were going to achieve a method for analysis cities by looking to characters (physical identity). Subjects of this paper were about the theoretical framework of content urban morphology with emphasis on methods and different perspectives about analyzing them. That also provides definitions about a quality of visual elements, aesthetic form, physical analysis and cognition of space, urban public spaces, physical characteristics that influence a clear image of the city, and finally townscape significance to give urban environment identity. Indeed, we are looking for comprehensive process and analytical model to suit their particular environment and conditions for urban character study, instead of using conventional analytical models. The method for each city can be distinct and unique, because it cannot be a comprehensive method to analyze and present understanding to all cities. This paper had argued the Kropf‟s method is one of the best instrument to introduce the main research indicates and general approach for historical cities